PRINSIP KEPEMIMPINAN KRISTEN DALAM MENINGKATKAN EFEKTIVITAS ORGANISASI GEREJA - Risto Rengnge’ Layuk; Elsa Putri Matangkin, Putri Ayu Lestari T., Yuyun, Kalvin Oyksel Wuisan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research delves into the role and implementation of Christian leadership principles in efforts to enhance the effectiveness of church organizations. By exploring the principles of service, transformational leadership, and the management of spiritual gifts, this study aims to evaluate their impact on the quality of church leadership and the efficiency in achieving spiritual goals. The research methodology includes theoretical analysis of these principles through literature review related to the topic of organizational effectiveness in line with Christian principles. The findings of this study provide a comprehensive overview of how Christian leadership principles influence interactions among church members, motivate active participation in ministry, and shape an organizational culture consistent with Christian values. The research findings contribute to both practical and theoretical understanding of the application of Christian leadership principles in enhancing the effectiveness of church organizations. The implications of this research involve practical recommendations for church leaders and the development of leadership models that focus on Christian principles to achieve spiritual growth and fulfill the mission of church ministry.